Jobsheet Learning Media Development of Stone and Concrete Working Practice Courses Building Engineering Education Program of Padang State University - Wahyu Hutria; Nurhasan Syah; Azwar Inra (EDUTEC : Journal of Education And Technology, 2021)
Jobsheet learning media is designed to improve student learning outcomes so that students can understand the overall material provided and help learn independently. This research aims to develop a Jobsheet learning medium in the course of Stone and Concrete Work Practices Building Engineering Education Study Program that is valid, practical, and effective. This research uses Research and Development (R&D)method with 4-D development model. The subject of the study was a building engineering education student who took a course in Working Practice of Stone and Concrete Semester January-June 2019. The results obtained in this study are as follows:(1) produce jobsheet learning media (2) Validity of Jobsheet learning media, declared valid on the content aspect with a value of 0.83 and valid on the aspect of media format with a value of 0.89, (3) Practicality of jobsheet learning media based on two responses lecturers expressed very practical with a percentage of 89.92% and based on 15 responses students expressed very practical with a percentage of 85.03%, (4) Jobsheet learning media, otherwise effective can improve the knowledge aspect of students who use Jobsheet seen from student learning outcomes and effectively improve aspects of student skills seen from results and practice reports. Based on the results of this study, it can be concluded that jobsheet learning media has been valid, practical and effective as a teaching material in the course of Working Practice of Stone and Concrete.